Medulloblastoma in pregnancy - Sneha Krishna; Adam Morton (Obstetric Medicine, 2026)
Cerebral malignancy is uncommon in pregnancy. Described here is a woman who was diagnosed with medulloblastoma at diagnosed at 19 weeks’ gestation, managed with antenatal debulking surgery and cranial radiotherapy, and postpartum craniospinal radiotherapy and adjuvant chemotherapy. The management of medulloblastoma is complex, balancing maternal treatment and fetal safety. The case highlights the importance of a multidisciplinary approach in rare conditions where there are no consensus guidelines for management.